TI_GERICHTE 52.2019.72 vom 10. Januar 2019 , Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio - TI Tribunale d'appello (2019)
Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio